BEYOND THE TEXT: A DISCOURSE ANALYSIS OF RELIGIOUS ISSUES WRITTEN BY AKSIN WIJAYA ON PESANTREN.ID - Jufri, Jufriyanto; Hudi, Saman; Ilyas, Muhammad (FAJAR Jurnal Pendidikan Islam, 2025)
This study aims to analyze the religious discourse constructed by Aksin Wijaya in his articles published on the Pesantren.id platform. The primary focus of this research is to identify how Aksin employs rhetorical strategies to convey religious messages to his audience. The research questions posed include how Aksin constructs a form of religious discourse that is acceptable to readers, and what rhetorical strategies are utilized in his writings. The method applied in this study is discourse analysis, using a rhetorical theory approach, which enables the researcher to explore the persuasive communication techniques employed by the author in his articles. The findings reveal that Aksin Wijaya successfully creates a dynamic and inclusive religious discourse by employing strategic word choices, a persuasive tone, and audience engagement to establish a closer connection with readers. The analyzed articles also demonstrate Aksin’s ability to present religious messages that are relevant to contemporary issues while maintaining the traditional values of the pesantren (Islamic boarding school) tradition. This research contributes to the understanding of digital religious discourse within the context of modern pesantren education.